Using augmented reality and learning factories to deliver effective manufacturing training programs - Afy-Shararah, Mohamed; Patsavellas, John; Salonitis, Konstantinos (Springer, 2024)
Augmented reality (AR) holds great promise in revolutionizing training methodologies across diverse fields, particularly in manufacturing. This paper proposes a morphology to support the integration of AR into learning factories, creating a symbiotic relationship that enhances training effectiveness and efficiency. The morphology introduces key characteristics such as target group, purpose, reality environment, technology, space, assessment, and system integration, tailoring AR applications to the specific needs of manufacturing training programs. The incorporation of AR within learning factories revolutionizes traditional pedagogical approaches. In addition, it enables realistic simulations, multi-sensory experiences, and remote collaboration between the different stakeholders involved. The paper offers a perspective on the value of AR as a tool in manufacturing training programs for knowledge development and skills acquisition. It emphasizes the importance of maintaining a balance between AR and traditional hands-on training, ensuring pedagogical alignment, considering ethical implications, and evaluating the sustainability and cost-effectiveness of AR integration in manufacturing education. Despite some challenges, the paper underscores the substantial benefits of AR in manufacturing training, heralding a transformative era in skill acquisition and knowledge transfer within the industrial landscape.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; Networking and Information Technology R&D (NITRD); 9 Industry, Innovation and Infrastructure